Attendance in the Canadian Hockey League: The impact of winning, fighting, uncertainty of outcome, and weather on junior hockey attendance - Rodney J. Paul; Andrew P. Weinbach; Nick Riccardi (International Journal of Financial Studies, 2019)
An attendance model is specified for the Canadian Hockey League (CHL), the top level of junior hockey in Canada with some teams located in the United States. The natural log of attendance is used as the dependent variable, with explanatory variables consisting of the timing of the game, team performance characteristics, uncertainty of outcome measures, and weather-related variables. Weekends and Mondays were the most popular days for games. Winning and fighting were shown to be popular team characteristics that drive attendance. Uncertainty of outcome plays little role, if any, in fan interest at this level, while precipitation significantly reduces attendance.
Keywords: Z20; D12; 330; attendance; hockey; fighting; uncertainty of outcome